Gerenciamento de resíduos odontológicos no serviço público - Hidalgo, Lidia Regina da Costa [UNESP]; Garbin, Artênio José Isper [UNESP]; Rovida, Tania Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (FapUNIFESP (SciELO), 2013)
Objective: was to investigate the process of waste management of dental public health service in eleven counties. Material and method: one researcher conducted the visits, and observations were recorded on a previously elaborated and tested. Result: We visited 50 health units, and none presented a copy of the waste management plan. Of the total 62% of businesses held the correct segregation of waste at the time of his generation. The presence of containers suitable for each type of waste generated at the dental office was observed in 74% and of those, 94% had adequate capacity for the type of waste generated. The identification of the type of waste in plastic containers and annotations identifying the establishment from which the waste was found in 8% and 6% respectively. Only 21% of establishments had appropriate locations, according to the current regulations for the storage of waste until collection was done outside. Conclusion: It was found in this study that the routine adopted by public oral health, regarding the management of healthcare waste had flaws.

Objetivo: Verificar o processo de gerenciamento dos resíduos odontológicos do serviço público de saúde em 11 municípios brasileiros. Material e método: Uma única pesquisadora realizou as visitas e as observações foram anotadas em um roteiro previamente elaborado e testado. Resultado: Foram visitadas 50 unidades de saúde, sendo que nenhuma apresentou cópia do plano de gerenciamento de resíduos. Do total de estabelecimentos, 62% realizavam a correta segregação dos resíduos no momento da sua geração. A presença de recipientes adequados a cada tipo de resíduo gerado no consultório odontológico foi observada em 74% dos estabelecimentos e, destes, 94% apresentavam capacidade adequada ao tipo de resíduo gerado. A identificação do tipo de resíduo nas embalagens plásticas bem como anotações identificando o estabelecimento gerador dos resíduos foram encontradas em 8% e 6%, respectivamente. Somente 21% dos estabelecimentos apresentavam locais apropriados, de acordo com as normas vigentes, para o armazenamento dos resíduos até que fosse feita a coleta externa. Conclusão: Constatou-se na presente pesquisa que a rotina adotada pela rede pública de saúde bucal, no que tange ao gerenciamento de resíduos de saúde, apresentou falhas.
Dental waste management in the public service
Keywords: Waste management; Dental waste; Medical waste; Public health; Gerenciamento de resíduos; Resíduos odontológicos; Resíduos de serviços de saúde; Saúde pública